(untitled) (Shiksha Shastra Saurabh, 2022)
The objective of this article is to compare the volleyball skills among the girl students of community and institutional secondary schools in western Nepal. It also hypothesizes that there is a significant difference in volleyball skills between them. The research was based on the quantitative descriptive design. Altogether 40 girl students were selected as respondents, and 20 girl respondents from each type of school were taken through a simple random sampling method. The AAHPER volleyball skill test was applied as a tool. These test items are the indicators of the volleyball skills of an individual whereas volleying, servicing, passing and set-up measure the volleying, servicing, passing, and setter accuracy skill on the target point respectively. While comparing mean scores, the girls of institutional schools were found better than those of their community school counterparts. Furthermore, was applied p-value of the t-test in each test item separately at a 0.05 level of significance. Thus, it has found no significant difference between both groups in setup and serving tests. In contrast, a significant difference was found in the passing and volleying tests, as well as a composite score. Hence, this paper concluded that there were found significant differences in volleyball skills between both girl groups on overall test items. Therefore, it is sufficient evidence to accept the hypothesis of this paper. This means the girls of a community school may be more involved in intramural and extramural volleyball competitions, as well as sporting activities.